Glycomimetics and Glycoconjugates in Drug Discovery - Nuno M. Xavier; Peter R. Andreana (MDPI AG, 2024)
This Special Issue of Pharmaceuticals presents one review and six original articles that are demonstrative of the importance of glycomimetics and glycoconjugates as privileged groups of carbohydrate-based molecules in the search for and development of bioactive substances for therapeutic/pharmaceutical purposes [...]